Using nanoparticles to prevent enamel wear. (June 2021) - Chen, Yan; Simon, Bradley T.; Opperman, Lynne A.; Renner, Peter; Parkinson, Dilworth; Sinyukov, Alexander; Liang, Hong
Abstract: The objective of this research is to study the feasibility using nanomaterials to prevent and/or repair wear of teeth. Canine teeth have thin enamel prone to dental wear, causing pain, tooth loss, and infection. This research developed a new teeth repair agent based on the tribochemically active nanoparticles. The presence and properties of synthesized repair agents were evaluated after applying the repair agents by rubbing (simulated chewing) between extracted dog teeth. Polyether modified alpha‑zirconium phosphate (α-ZrP) nanoparticles form a strong and durable protective layer on a canine tooth's enamel surface through chewing. The effectiveness of this protective film generation was enhanced by adding hydroxyapatite (HAp) nanoparticles into the repair agent. This protective film is up to 2 μm thick and has a hardness comparable to the enamel substrate. These results show that by chewing with the repair agent, the teeth are protected. The tomography result shows this repair agent also has the potential to mend cracks on the enamel surface. This research reports a novel approach to protect the wear of teeth. Nanoparticles promoted the generation of a protective film in situ during the chewing process. This nanomaterial can be the base of novel dental protective devices such as chewing toys or gums that preventing or reversing tooth wear and reducing the stress and cost of dental restoration operations. Highlights: Nanomaterials to prevent and treat enamel wear in response to frictional forces. Polyether modified nanoparticles forms a hard-protective coating when chewed. Forms protective coating up to 2 μm thick and as hard as enamel. This nanomaterial can be the base of novel dental protective devices.